2021
DOI: 10.1002/ijgo.13814
|View full text |Cite
|
Sign up to set email alerts
|

Erosive vulvo–vaginal lichen planus treated with rituximab: A case report

Abstract: SynopsisRituximab is an effective treatment for erosive vulvo–vaginal and oral lichen planus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Whereas the pathogenic role of IgG anti-BP180 has been validated in BP ( 50 ), their pathogenicity is less demonstrated in MMP, but rituximab efficacy was reported in a large series ( 51 ). On the other hand, rituximab efficacy has been uncertain in small series of erosive lichen planus without AIBD, whose immunopathology is more T cell driven ( 52 , 53 ). This may explain why the two patients who received rituximab still had active disease.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the pathogenic role of IgG anti-BP180 has been validated in BP ( 50 ), their pathogenicity is less demonstrated in MMP, but rituximab efficacy was reported in a large series ( 51 ). On the other hand, rituximab efficacy has been uncertain in small series of erosive lichen planus without AIBD, whose immunopathology is more T cell driven ( 52 , 53 ). This may explain why the two patients who received rituximab still had active disease.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy also demonstrated complete remission of esophageal involvement at month 3 [ 158 ]. Three additional case reports of four patients with refractory oral and vulvovaginal erosive LP reported successful treatment with rituximab [ 159 – 161 ]. One case report of lichen planopilaris in a patient with juvenile chronic arthritis described rapid and complete resolution with rituximab treatment [ 162 ]; however, a retrospective study of five patients with refractory erosive LP reported failure or transient minimal improvement with rituximab.…”
Section: Autoimmune Diseases Of the Skinmentioning
confidence: 99%